New Trends in Enhanced, Hybrid and Integrated Geothermal Systems - Nathwani, Jatin; Dehghanisanij, Alireza (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Geothermal energy is a renewable, sustainable, and ecologically friendly resource of energy that can be captured with shallow or deep installations, or a combination of both-alone or integrated with other technologies. It can then be employed for a variety of purposes, for example, electricity generation, space heating and cooling, agriculture, and aquaculture. Given the nature/features of this green energy resource-such as being a local, climate-independent, potentially constant, robust, generally available, resilient, almost greenhouse gas-free, and long-lived energy source-geothermal solutions can and should make a more prominent contribution to the future global energy supply mix, in addition to helping lessen humanity's environmental footprint and enabling it to attain its sustainable development goals. This Special Issue, "New Trends in Enhanced, Hybrid and Integrated Geothermal Systems", addresses existing knowledge gaps and aids advance deployment of geothermal energy globally. It consists of eight peer-reviewed papers that cover a range of subjects and applications related to geothermal energy.